Challenges And Opportunities In Generic Drug Market Expansion Across Developing Nations - Srinivasan, Vaibhava; Sinha, Praveen Kumar; Sunkara, Sreenivasulu (Journal of Neonatal Surgery, 2025)
The expansion of the generic drug market in developing nations presents a complex interplay of challenges and opportunities that significantly impact healthcare accessibility, affordability, and sustainability. This study examines the multifaceted factors influencing the growth of the generic pharmaceutical industry, focusing on regulatory frameworks, intellectual property rights (IPR), supply chain inefficiencies, infrastructure limitations, and economic instability. Employing a descriptive and exploratory research design, the study analyzes data from secondary sources using correspondence analysis to identify key themes and relationships. The findings reveal that regulatory barriers, such as lengthy approval processes and inconsistent policies, alongside IPR constraints, particularly patent protections and legal disputes, hinder the timely introduction and affordability of generic medicines. Supply chain disruptions, inadequate healthcare infrastructure, and economic volatility further compound these challenges, limiting the availability and distribution of generic drugs. However, the study also highlights growth opportunities through government interventions, public-private partnerships, and technological advancements like artificial intelligence and blockchain, which can streamline regulatory processes, improve supply chain efficiency, and enhance drug quality assurance. Additionally, the research underscores the importance of understanding market dynamics, consumer perceptions, and pricing strategies in shaping the acceptance and sustainability of generic medicines. The study offers valuable insights for policymakers, pharmaceutical companies, and healthcare stakeholders in navigating the complexities of the generic drug market, emphasizing the need for collaborative efforts to promote equitable access to affordable, quality medicines in developing nations.